2015
DOI: 10.1016/j.rdc.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vasculitis

Abstract: Pulmonary vasculitis encompasses inflammation in the pulmonary vasculature with involved vessels varying in caliber from large elastic arteries to capillaries. Small pulmonary capillaries are the vessels most commonly involved in vasculitis affecting the lung. The antineutrophil cytoplasmic antibody-associated vasculitides, which include granulomatosis with polyangiitis (formerly Wegener granulomatosis), microscopic polyangiitis, and eosinophilic granulomatosis with polyangiitis (formerly Churg-Strauss syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 83 publications
(91 reference statements)
0
12
0
1
Order By: Relevance
“…ANCA-associated vasculitis (AVV) is a life-threatening condition and patients typically sustain renal and pulmonary injury ( Holguin et al, 2008 , Lally and Spiera, 2015 , Cid, 2012 ). It has further confirmed that the impaired endothelial function contributes to the development and progression of diverse vascular, inflammatory, and pulmonary hemorrhage ( Verma et al, 2003 , Dzau et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…ANCA-associated vasculitis (AVV) is a life-threatening condition and patients typically sustain renal and pulmonary injury ( Holguin et al, 2008 , Lally and Spiera, 2015 , Cid, 2012 ). It has further confirmed that the impaired endothelial function contributes to the development and progression of diverse vascular, inflammatory, and pulmonary hemorrhage ( Verma et al, 2003 , Dzau et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…El retorno hemorrágico seriado del lavado broncoalveolar, confirma el diagnóstico de HAD. La presencia de hemosiderofagos >20% es compatible con este diagnóstico, pero tiene una especificidad limitada para determinar la causa de la enfermedad [9] . Se diferencian tres entidades, según hallazgos histopatológicos: capilaritis pulmonar, hemorragia alveolar blanda y daño alveolar difuso, siendo la primera la más común [3,10,11] .…”
Section: Discussionunclassified
“…atherosclerosis), pulmonary hypertension (PH), or post-stenotic dilatation from pulmonic valve stenosis. 10 , 11 Systemic vasculitides may involve the large pulmonary arteries leading to PAA, 12 but this is rarely an isolated finding without evidence of vasculitis elsewhere.…”
Section: Discussionmentioning
confidence: 99%